THE ENHANCEMENT OF JUNIOR HIGH SCHOOL STUDENTS MATHEMATICAL SPATIAL SENSE ABILITIES THROUGH COMPUTER-BASED INTERACTIVE MULTIMEDIA INSTRUCTION - Nurjanah, Nurjanah; Suryadi, Didi; Sabandar, Jozua; Darhim, Darhim (UPI Press, 2014)
Geometry is a basic mathematical concept studied at all education levels. However empiricalevidence suggests there are many students who have difficulties learning geometry. One ofmany factors that enhances the success of students’ understanding of geometry is students’ senseof spatial ability. Seeking ways to support students’ development of spatial sense, researchersstudied the impact of Computer-Based Interactive Multimedia Instruction. This study was quasiexperimental in nature with Pretest and Post-test Control Group Design. The participants of thestudy were second grade students of two public junior high schools that were classified as schoolsof high and middle level ranking, in Bandung. The instruments utilized in this study consistedof prior mathematical skills test (KAM) and spatial sense ability test. The results suggested that:(1a) generally the students’ spatial sense ability and learning independency were enhanced usingComputer-Based Interactive Multimedia Instruction, compared with conventional learning;(1b) there were no differences in the enhancement achievements between students’ spatial senseability and conventional learning related to school ranking level; (1c) according to KAM, therewere significant enhancements of student’s spatial sense ability between high, middle, and lowKAM; (2) There is no interaction of effect between learning (CBIM and CVL) and school levelto the enhancement of ability of students’ spatial sense. (3) There is no interaction of effectbetween learning (CBIM and CVL) and KAM to the enhancement of ability of students’ spatialsense.Keywords: geometry, spatial sense, computer-based interactive multimedia, learning difficulties.